The Role of Attachment in Parents’ Perception of the Impact of Pediatric Cancer on Their Relationship - Laplante, Sabrina; Beaulieu, Noémie; Sultan, Serge; Péloquin, Katherine (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2024)
Introduction: The cancer diagnosis of a child is an extremely challenging event that necessitates adjustments for parents at individual, family, and couple levels. To our knowledge, the factors that may explain parents’ relationship adjustments in the context of pediatric cancer remain under-documented.Objectives: This dyadic study (1) described the perceived impact of pediatric cancer on parents’ relationship and (2) explored the relationship between attachment insecurities (both anxiety and avoidance) in both parents and their perception of how pediatric cancer influenced different facets of their relationship.Method: Fifty-one mixed-sex couples whose child has received treatment for cancer (whether the treatment was ongoing or completed) within the past two years, completed online questionnaires.Results: Path analyses, based on the Actor-Partner Interdependence Model, showed that higher attachment insecurities in mothers and fathers were associated with their own perception of a more negative impact of cancer on their relationship regarding the quality of partner support (actor effect). Surprisingly, higher attachment insecurities in mothers and fathers were also linked to their partner’s perception of a more positive impact of their child’s illness on their relationship functioning (partner effects).Discussion and conclusion: These results suggest that attachment insecurities not always have solely negative impacts. In extreme situations, such as pediatric cancer (at least in the early years of post-diagnosis), attachment-related anxiety and avoidance of parents could protect the relationship from certain difficulties.